(untitled) (Indian Journal of Fibre & Textile Research (IJFTR), 2025)
Thermo-physiological comfort is related to the body’s heat balance at different activity levels. In extremely cold weather conditions, it is essential that the inner layers of the ensemble transport the liquid sweat and water vapours generated by human skin away from the body and keep the skin dry. The soldiers must carry heavily loaded bags, so the fabric’s compressional recovery property is vital to regain its thickness and insulation. Fleece fabric is one of the components of clothing in extreme cold climates. The major function of the fleece fabric is to transport the liquid from the skin side to the base side of the fabric and entrap still air to provide some insulation. The incorporation of air channels in the fleece fabric is responsible for the vapour transmission and air entrapment, as well as reducing the weight of the fabric. In the present work, we have developed a few grid fleece fabrics by varying the combination of filament and spun yarns, differing in yarn and fibre fineness in the base and fleece parts of the fabrics. The effect of fibre fineness, yarn fineness and yarn structure (spun or filament) on moisture transport, thermal insulation and compressional properties are studied. The findings suggest that fleece fabric with filament yarn on the base side and spun yarn on the fleece side have better moisture management properties.